Application of Isotope Tracer in Cross-Well Nanometre Tracer Testing. (6th August 2022) - Pang, Yang; Zhao, Lin; Song, Yushou; Wei, Guang; Han, Yehui; Wang, Qiang
Abstract : In order to understand the dynamic monitoring characteristics and heterogeneity characteristics of injection production wells in the monitoring area and judge the reservoir connectivity, this study puts forward the application method of isotope nanometre tracer in interwell nanometre tracer testing. The trace material nanometre tracer interwell monitoring technology was applied to well block J in a basin. Through the analysis of the morphological characteristics of the nanometre tracer production curve and the quantitative interpretation of trace material tracer, combined with the analysis of the advancing speed of the water line at the front edge of the nanometre tracer and the distribution of injected water wells, the nanometre tracer connectivity, and advancing speed, the characteristics of seepage channels and heterogeneity of the well groups in the study area were defined. The research results show that 8 oil wells in the monitoring area are controlled by water injection well J1, the injection water inrush direction is generally north, the main channel of injection water is mainly high-permeability strip, and the heterogeneity contradiction between layers is strong. It is recommended to adopt mild water injection. Conclusion . This study found that the dynamic connectivity between oil and water wells in the monitoring area is good.